Milkman - Burns, Anna. (London : Faber & Faber, 2018)
"In an unnamed city, middle sister stands out for the wrong reasons. She reads while walking, for one. And she has been taking French night classes downtown. So when a local paramilitary known as the milkman begins pursuing her, she suddenly becomes "interesting," the last thing she ever wanted to be. Despite middle sister's attempts to avoid him-- and to keep her mother from finding out about her maybe-boyfriend-- rumors spread and the threat of violence lingers. Milkman is a story of the way inaction can have enormous repercussions, in a time when the wrong flag, wrong religion, or even a sunset can be subversive"--Container.
Keywords: Young women -- Fiction; Sisters -- Fiction; Stalking -- Fiction; Gossip -- Fiction; Gossip; Young women; FICTION / Literary